Phytochemical profile and antioxidant activity of Dracocephalum kotschyi boiss. affected by environmental conditions of cultivation regions - Sahar Zamani; Davood Bakhshi; Mohammad-Taghi Ebadi; Amir Sahraroo (BMC Plant Biology)
Abstract Dracocephalum kotschyi is a medicinal plant rich in antioxidant phytochemicals. Identifying the suitable cultivation region and evaluating the impact of environmental factors can help in choosing the best conditions for the commercial production of these herbs. The present study investigated the effect of different cultivation areas, Lasak (LSK), Saravarsu (SVS), and Sorkh Geriveh (SGV) on the glandular trichome density and phytochemicals of D. kotschyi. According to the findings, the environmental factors significantly affected the plant phytochemicals. The highest glandular trichome density (16 number mm−2), essential oil content and yield (0.716% and 0.45 g m−2), geraniol (24.3%), citral (16.2%), cis-carveol (13.2%), α-pinene (12%), methyl generate (7.2%), geranyl acetate (7.1%), PAL activity (10.104 nmol min−1 g−1 FW), total phenol (2.036 mg GAE g−1 DW), coumaric acid (0.112 mg g−1 DW), rutin (29.688 mg g−1 DW), rosmarinic acid (9.668 mg g−1 DW) and apigenin (8.089 mg g−1 DW) were recorded in the SGV region so that was up to 100-fold higher than in the LSK region. Finally, the environmental conditions of the SGV region (higher altitude, lower temperature, rainfall, and humidity, as well as some soil characteristics) strongly increased the production of phytochemicals, so this region is suggested for the commercial production of this plant and its secondary metabolites for various industries.